2018
DOI: 10.1002/mrd.23063
|View full text |Cite
|
Sign up to set email alerts
|

miR‐34 regulates reproduction by inhibiting the expression of MIH, CHH, EcR, and FAMeT genes in mud crab Scylla paramamosain

Abstract: Mud crab Scylla paramamosain is a commercially important species widely cultured in China. It is well known that the eyestalk regulates reproductive activities in crustaceans. In our previous research, we found that the miR‐34 expression level in male eyestalk was significantly higher than that in females. Thus, we assumed that it may play an important role in regulating reproduction. In this study, we used bioinformatic tools to identify the target genes of miR‐34 in eyestalk. Six reproduction‐related genes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Localization studies indicated that FAMeT is co-localized in the neurosecretory cells that produce CHH and MIH. Higher levels of FAMeT mRNA transcript and protein levels were reported along with higher levels of CHH and GIH (Zhou et al, 2019). MF biosynthesis is regulated by secreted neuropeptides from the X-organ which regulates the activity of FAMeT and thereby vitellogenesis (Gunawardene et al, 2002).…”
Section: Regulatory Mechanism Of Sex In Female Decapods Upstream Mechanisms Of Sex In Female Decapodsmentioning
confidence: 98%
See 4 more Smart Citations
“…Localization studies indicated that FAMeT is co-localized in the neurosecretory cells that produce CHH and MIH. Higher levels of FAMeT mRNA transcript and protein levels were reported along with higher levels of CHH and GIH (Zhou et al, 2019). MF biosynthesis is regulated by secreted neuropeptides from the X-organ which regulates the activity of FAMeT and thereby vitellogenesis (Gunawardene et al, 2002).…”
Section: Regulatory Mechanism Of Sex In Female Decapods Upstream Mechanisms Of Sex In Female Decapodsmentioning
confidence: 98%
“…The major source of these neuropeptides is the X-organ located in the eyestalk ganglia. These neuropeptides involved in carbohydrate and lipid metabolism, moulting, and ovarian development (Böcking et al, 2002;Zhou et al, 2019). The RPCH is not only involved in the regulation of pigmentation but also the regulation of ovarian maturation in crustaceans (Fingerman, 1997).…”
Section: Regulatory Mechanism Of Sex In Female Decapods Upstream Mechanisms Of Sex In Female Decapodsmentioning
confidence: 99%
See 3 more Smart Citations